Racing fast and slow: Defining the tactical behavior that differentiates medalists in elite men's 1,500 m championship racing - Sandford, G. N.; Day, B. T.; Rogers, S. A. (Frontiers in Sports and Active Living, 2019)
Background: 1,500 m running has long been a blue ribbon event of track championship racing. The eventual medalists employ common tactical behaviors such as a fast sustained pace from the start (gun-to-tape), or, slow initial laps that precede a precisely timed race kick. Before the kick, there are positional changes caused by surging, that can go uncharacterized. The inter-relationship of surge events, tactical positioning, and kick execution may have important implications for eventual medal winning outcomes and require further definition.